Pengaruh Dimensi Islam Terhadap Kepuasan Konsumen di Hotel Indah Syariah Sibuhuan - Amir Hasan Hasibuan; Abd Manap Ht Uruk; Nurjannah Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Abstract.The purpose of this research is to find out: (1) How the Islamic dimension of service affects consumer satisfaction at the Indah Syariah Sibuhuan Hotel, (2) Is there an influence of the Islamic dimension on consumer satisfaction at the Indah Syariah Sibuhuan Hotel. The type of research used in this research is quantitative research. In this quantitative method, research is carried out directly in the field or at the research location. The research approach used in this research is in the form of a direct survey to customers. Surveys are carried out by distributing questionnaires to customers. The results of this research show that the Islamic dimension of service on consumer satisfaction at the Indah Syariah Sibuhuan Hotel is very influential. The better the Islamic dimension of service provided, the higher the level of satisfaction when using the services of the Indah Syariah Sibuhuan Hotel. Hotel Indah Syariah Sibuhuan consistently provides high quality services to consumers, so that consumers feel satisfied with the service they receive. Aspects of service such as reliability, trust, appearance, empathy and responsiveness offered by the hotel, these are the Islamic dimension variables partially have a positive and significant effect on consumer satisfaction at the Indah Syariah Sibuhuan Hotel. With the regression coefficient for the Islamic dimension variable (X) being positive, the resulting t value of 5.076 is more than the t table of 1.672 with a significance of less than 0.558. This means that the Islamic Dimension variable (X) partially has a positive and significant effect on Consumer Satisfaction (Y).